How many species of Hipposideros have occurred on Madagascar since the Late Pleistocene?. (20th May 2016) - Goodman, Steven M.; Schoeman, M. Corrie; Rakotoarivelo, Andrinajoro; Willows‐Munro, Sandi
Abstract : Populations of the Malagasy H ipposideros commersoni (family Hipposideridae) are threatened by deforestation and hunting. Maximum likelihood and Bayesian analysis of 148 cytochrome b sequences found this species to be paraphyletic and composed of three well‐supported monophyletic clades. Clades B and C form a monophyletic lineage that can be referred to H. commersoni ; these two clades are separated by 6% sequence variation. Clade A represents a distinct evolutionary lineage separate (9–11% average sequence divergence) from H. commersoni (clades B and C) and is named herein as a new species, H ipposideros cryptovalorona sp. nov. In the phylogeny presented herein, this species is strongly associated with the outgroup taxa H ipposideros gigas and H ipposideros vittatus, both restricted to Africa. External, cranial and dental measurements taken from the same individuals used in the molecular study indicate no clear distinction in morphology amongst these three clades; this includes noseleaf structure and craniodental characteristics. Principal component analyses showed limited separation of the three clades. Comparison to a Quaternary fossil species from north‐west Madagascar, H ipposideros besaoka, found little morphological overlap between any of the three clades and this extinct species. Hence, at least three species of H ipposideros have occurred on Madagascar since the Late Pleistocene, two extant ( H . commersoni s.s . and H. cryptovalorona sp. nov.) and one extinct ( H . besaoka ). © 2015 The Linnean Society of London